2009
DOI: 10.1111/j.1551-2916.2008.02790.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ceramics from Metakaolin‐Based Geopolymers: Part I—Cs‐Based Geopolymer

Abstract: The structural evolution and crystallization of a cesium-based geopolymer (Cs 2 O . Al 2 O 3 . 4SiO 2 . 11H 2 O) on heating was studied by a variety of techniques including X-ray diffraction, thermal analysis, dilatometry, pycnometry, specific surface area, and microstructural investigation. The Cs geopolymer gradually crystallized into pollucite (Cs 2 O . Al 2 O 3 . 4SiO 2 ) on heating above 9001C. Its low crystallization temperature is believed to be due to the presence of nuclei in the geopolymer precursor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 47 publications
8
119
2
2
Order By: Relevance
“…When treated at 1400°C, those composites tend to fracture in a very brittle manner owing to the seriously degraded carbon fibers together with matrix melting and crystal phases dissolve. Bell et al [15] prepared Cs-based geopolymer through cesium silicate solution and found Cs geopolymer gradually crystallized into pollucite on heating above 900°C. These studies help us obtained some important information on geopolymer at higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When treated at 1400°C, those composites tend to fracture in a very brittle manner owing to the seriously degraded carbon fibers together with matrix melting and crystal phases dissolve. Bell et al [15] prepared Cs-based geopolymer through cesium silicate solution and found Cs geopolymer gradually crystallized into pollucite on heating above 900°C. These studies help us obtained some important information on geopolymer at higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This route to ceramic production has advantages associated with high green (unfired) strength and increased dimensional stability during the sintering process when compared to conventional ceramic production involving powder pressing and sintering. 3 Previous work on the effect of high temperatures on geopolymers has examined phase changes using XRD and NMR [15][16][17][18][19][20]. Different charge balancing cations (Na, K and Cs)…”
Section: Introductionmentioning
confidence: 99%
“…Other utilisation of alkali-activation in the area of radioactive or nuclear fuel cycle-related waste treatment has included the solidifi cation of spent ion exchange resins [ 125 ], and S/S treatment of radioisotopes including 152 Eu, 60 Co and 59 Fe [ 196 ] 99 Tc [ 197 , 198 ] and 129 I [ 198 ]. This does appear to be an area in which the versatility of alkali-activation chemistry, in developing matrices based either on calcium-silicate chemistry or alkali-aluminosilicate chemistry, or a mixture of the two gel types, can provide advantages over purely calcium silicate-based systems, particularly if water removal (by moderate-temperature heat treatment) to prevent radiolytic hydrogen generation is desired.…”
Section: Stabilisation/solidifi Cation Of Radioactive Wastesmentioning
confidence: 99%